SUMBANGAN ETIKA GLOBAL HANS KÜNG DEMI TERWUJUDNYA PERDAMAIAN DAN RELEVANSINYA BAGI INDONESIA - Reinardus L Meo (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: This article is aimed at introducing Hans Küng’s globalethic and its contributions to world peace. Various crises whichhave hit and are hitting the world motivated Küng to againstruggle to bring peace about and to establish a new, better lifeorder. By a global ethic – a basic consensus on binding values, noncancellablecriteria, and basic attitudes which are affirmed by allreligions, although dogmatically they are different, and which canactually be given by non-believers – Küng emphasizes importantroles of religions without disregarding non-religious communities,which are principally present to bring peace about as the maincharacteristic of their teachings. Specifically, Küng’s opinion isrelevant in an effort to bring peace about in Indonesia, which isvery plural. Realizing that threats against peace and plurality inIndonesia often come and result from interreligious conflicts, adialogue is absolutely necessary. As a concrete form of a globalethic, Küng suggests a critical dialogue. Representatives of thereligions in Indonesia need to step forward and sit together in agive-and-take dialogue which introduces the special aspect andmain direction of each of the religions. Followers’ steadfastnessin the principles and seriousness in following the religions aretwo main keys to a critical dialogue, which can penetrate thefoundation of each religion with all of its consequences.Keywords: Peace, Crisis, Global Ethic, Religion, Critical Dialogue